Regional gray matter abnormalities in pre-adolescent binge eating disorder: A voxel-based morphometry study. (April 2022) - Murray, Stuart B.; Duval, Christina J.; Balkchyan, Ane A.; Cabeen, Ryan P.; Nagata, Jason M.; Toga, Arthur W.; Siegel, Steven J.; Jann, Kay
Highlights: The neurobiology of preadolescent binge eating disorder is largely unknown. Children with binge eating disorder show diffuse elevations in gray matter density. Abnormalities in cortical morphometry may reflect abnormal arborization and synaptic pruning. Abstract: Background: Binge eating disorder (BED) is a pernicious psychiatric disorder which is linked with an array of multisystemic organ morbidity, broad psychiatric morbidity, and obesity. Despite behavioral markers often developing in early childhood, the neurobiological markers of early-onset BED remain understudied, and developmental pathophysiology remains poorly understood. Methods: 71 preadolescent children (aged 9–10-years) with BED and 74 age, BMI and developmentally matched control children were extracted from the 3.0 baseline (Year 0) release of the Adolescent Brain Cognitive Development (ABCD) Study. We investigated group differences in gray matter density (GMD) via voxel-based morphometry (VBM). We additionally performed region of interest analyses, assessing the association between GMD in nodes of the reward (orbitofrontal cortex; OFC) and inhibitory control (dorsolateral prefrontal cortex; dlPFC) networks, and parent-reported behavioral inhibition and approach tendencies. Results: Diffuse elevations in cortical GMD were noted in those with BED, which spanned prefrontal, parietal, and temporal regions. No areas of reduced GMD were noted in those with BED. No alterations in subcortical GMD were noted. Brain-behavioral associations suggest a distinct and negative relationship between GMD in the OFC and dlPFC, respectively, and self-reported markers of hedonic behavioral approach tendencies. Conclusions: Early-onset BED may be characterized by diffuse morphological abnormalities in gray matter density, suggesting alterations in cortical architecture which may reflect decreased synaptic pruning and arborization, or decreased myelinated fibers and therefore inter-regional afferents.